Pengaruh Metode Pembelajaran Dual Coding dalam Bentuk Audiovisual terhadap Tingkat Pemahaman Belajar pada Siswa Kelas V & VI di SDN 2 Korowelanganyar - Lulus Anggun Listiyani; Anissahrotul Hidayah; Masna KhoerotuNisa; Fitria Handayani; M. Alwi Athoillah; Misbahudin Efendy; Dicky Hastana Atmaja (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This study aims to examine the effect of applying Dual Coding-based audiovisual learning methods on the learning comprehension of fifth- and sixth-grade students at SDN 2 Korowelanganyar. The research background arises from the issue of low student understanding due to monotonous teaching methods and lecture dominance. Dual Coding integrates verbal (audio) and visual (images, videos) channels, making information easier to process and retain. This research employed a quantitative approach with a quasi-experimental design, namely the Nonequivalent Control Group Design. A total of 60 students were involved, divided into experimental and control groups. Data were collected through pretest and posttest, then analyzed using a t-test. Results indicated no significant difference between groups in the pretest. However, the posttest revealed a significant difference, with the experimental group achieving a higher mean score (94.67) compared to the control group (84.00). These findings demonstrate that audiovisual Dual Coding significantly improves students’ learning comprehension. Therefore, this method can serve as an effective and interactive learning strategy aligned with the cognitive development of elementary school students.